Inverse MultiView. II. Microarcsecond Trigonometric Parallaxes for Southern Hemisphere 6.7GHz Methanol Masers G232.62+00.99 and G323.74–00.26 - Hyland, LJ; Reid, MJ; Orosz, G; Ellingsen, SP; Weston, SD; Kumar, J; Dodson, R; Rioja, MJ; Hankey, WJ; Yates-Jones, PM; Natusch, T; Gulyaev, S; et al. (American Astronomical Society, 2023)
We present the first results from the Southern Hemisphere Parallax Interferometric Radio Astrometry Legacy Survey: 10 μas accurate parallaxes and proper motions for two Southern Hemisphere 6.7 GHz methanol masers obtained using the inverse MultiView calibration method. Using an array of radio telescopes in Australia and New Zealand, we measured trigonometric parallaxes and proper motions for the masers associated with the star formation region G232.62+00.99 of π = 0.610 ± 0.011 mas, μx = −2.266 ± 0.021 mas yr−1, and μy = 2.249 ± 0.049 mas yr−1, which implies its distance to be d = 1.637 ± 0.029 kpc. These measurements represent an improvement in accuracy by more than a factor of 3 over the previous measurements obtained through Very Long Baseline Array observations of the 12 GHz methanol masers associated with this region. We also measure the trigonometric parallax and proper motion for G323.74–00.26 as π = 0.364 ± 0.009 mas, μx = −3.239 ± 0.025 mas yr−1, and μy = − 3.976 ± 0.039 mas yr−1, which implies a distance of d = 2.747 ± 0.068 kpc. These are the most accurate measurements of trigonometric parallax obtained for 6.7 GHz class II methanol masers to date. We confirm that G232.62+00.99 is in the Local Arm and find that G323.74–00.26 is in the Scutum–Centaurus arm. We also investigate the structure and internal dynamics of both masers.
Keywords: 5101 Astronomical Sciences; 51 Physical Sciences; 0201 Astronomical and Space Sciences; 0202 Atomic, Molecular, Nuclear, Particle and Plasma Physics; 0306 Physical Chemistry (incl. Structural); Astronomy & Astrophysics; 5101 Astronomical sciences; 5107 Particle and high energy physics; 5109 Space sciences